Effect of halide mineralizers on monodisperse spherical zircon powders. Issue 6 (9th February 2021) - Peng, Shan; Yang, Hui; Chen, Zhongqiu; Huang, Qing; Xia, Xiaohong; Wang, Zhuo; Huang, Zhongbing; Homewood, Kevin P.; Gao, Yun; Lei, Binglong
Abstract: Zircon has been widely applied in various traditional and emerging fields due to its distinct physiochemical advantages while monodisperse spherical zircon (MSZ) powders hitherto have not been explored for the tremendous challenges in the control of zircon crystallization and growth. Herein, systematic investigations are presented to reveal the paramount role of halide mineralizers upon the crystallization and growth of MSZ powders synthesized under highly acidic hydrothermal environments (pH <0). A formation mechanism is revealed revolving around the complexation of central Zr 4+ with the Lewis basic ligand, fluorine, which forms the F‐containing species of [(OH)1–y ·Ry ] (R = F, Cl) to replace Zr and generates Zr‐deficient zircons as (ZrO4 )1‐x Si[(OH)1‐y ·Ry ]4x . This finding differs much from conventional views on common fluoro‐hydroxylated hydrothermal zircons, which were generally regarded as Si‐deficient silicates from the substitution of fluoro‐hydroxyls for the [SiO4 ] tetrahedra. A parameter, K r =4xy, is first proposed as an index to evaluate the stability of hydrothermal zircons. The MSZ powders demonstrate superb thermal stability at high temperature, superior photo‐reflectance, and thermal insulation over normal zircons, promising attractive prospects to extend zircon applications.